Bolder together: conformity drives behavioral plasticity in eastern gartersnakes - Morgan Skinner; Gokulan Nagabaskaran; Tom Gantert; Noam Miller (Animal Cognition)
Abstract Personality traits drive individual differences in behaviour that are consistent across time and context. Personality limits behavioural plasticity, which could lead to maladaptive choices if animals cannot adapt their behavior to changing conditions. Here, we assessed consistency and flexibility in one personality trait, boldness, across non-social and social contexts in eastern gartersnakes (Thamnophis sirtalis sirtalis). Snakes explored a novel open arena either alone or in a pair. Pairs were assigned based on the data from the solo trials, such that each snake was paired once with a bolder and once with a less bold partner. We predicted that snakes would conform when in a social context, displaying plasticity in their personality, and causing boldness scores to converge. We found that snakes were consistent within contexts (solo or paired), but changed their behavior across contexts (from solo to paired). Plasticity in boldness resulted from an interaction between conformity and repeatable individual differences in plasticity. In line with some data on other species, snakes conformed more when they were the less bold partner. Personality reflects a consistent bias in decision-making, but our results highlight that the cognitive processes that drive the expression of personality traits in behavior are flexible and sensitive to social context. We show that both consistency and plasticity combine to shape snake social behavior in ways that are responsive to competition. This pattern of behavior may be particularly beneficial for species in which group-living is seasonal.